Changing agriculture- changing landscape: what is going on in the high nature valued Montado landscapes of southern Portugal? - Pinto-Correia, Teresa (2014)
The Portuguese montado is a particular land use system, characterized by the combination, in the same area, of the forestry and the grazing components interrelating with each other, in large-scale farm units. Mostly, this system is acknowledged due to its specific landscape character, in a savanna-like phisionomy, with changing densities along a continuous tree cover of holm and cork oaks and grazing in the under cover. The montado is a production system, and its extensive character and particular pattern makes it possible to support a multitude of ecosystem goods and services nowadays valued by society. Nevertheless the system is threatened and the resulting landscape is under strong reduction in the last decades. This paper shows the dimension of the ongoing reduction, for the whole region of Alentejo, since 1960 and up to now. And furthermore, based on a survey to land managers of montadoin a Natura 2000 site, it shows how the land management options for the most are still focusing on production and productivist ideals, even when keeping a multifunctional system. These orientations do not result in a radical replacement of the system, and therefore the illusion is kept that the multifunctionality is mantained – but progressively the system loses its balance and the tree cover decays in such a way that the montado disappears. This unique landscape is thus under severe threat. The paper ends with a discussion on the urgent need for integrated policy goals and tools for the montado as a system, and for much more colaboration with the land managers in order to strength the multifunctionalty relevance and support a novel attitude replacing the productivist concept of farming, misleading in the context of this system.